Erosion Corrosion Behavior of Several Typical Pipeline Materials in Flowing Seawater - WU Xing - wei, NIE Lei - xin, WU Heng (Cailiao Baohu, 2021)
In order to verify the erosion and corrosion resistance of several different common seawater pipelines in ship, the erosion and corrosion resistance characteristics of 4 kinds of pipelines material were tested in the seawaters flows with different flow rates. The corrosion resistance of 907 steel, 316L stainless steel, B10 copper - nickel alloy, and TA2 titanium alloy pipeline at the flow rate of 1, 3, and 5 m/s was analyzed by the means of corrosion weight loss, potential measurement, and potentiodynamic polarization. Results showed that TA2 presented no obvious corrosion weight loss under 1, 3, 5 m/s, while the corrosion rate of B10, 316L, and 907 increased with the increase of flow rate. In the TA2 scour test, the stable potential had a certain positive trend with the increase of the scouring speed, and the potential was always the most positive. Meanwhile, the potentials of B10, 316L, and 907 had no significant change with the increase of flow rate. In terms of corrosion, TA2 material possessed good corrosion resistance, which could be an ideal pipe material for seawater scour resistance.